2002
DOI: 10.1128/aem.68.10.5136-5141.2002
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Efficient Production of Ethanol from Cellulosic Material with a Yeast Strain Displaying Cellulolytic Enzymes

Abstract: For direct and efficient ethanol production from cellulosic materials, we constructed a novel cellulosedegrading yeast strain by genetically codisplaying two cellulolytic enzymes on the cell surface of Saccharomyces cerevisiae. By using a cell surface engineering system based on ␣-agglutinin, endoglucanase II (EGII) from the filamentous fungus Trichoderma reesei QM9414 was displayed on the cell surface as a fusion protein containing an RGSHis6 (Arg-Gly-Ser-His 6 ) peptide tag in the N-terminal region. EGII act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(96 citation statements)
references
References 20 publications
3
90
0
3
Order By: Relevance
“…To facilitate direct ethanol fermentation from cellulose, we previously developed yeast strains displaying cellulolytic enzymes on the cell surface [5,10]. In this study, to increase ethanol productivity, we optimized the cellulase expression system.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate direct ethanol fermentation from cellulose, we previously developed yeast strains displaying cellulolytic enzymes on the cell surface [5,10]. In this study, to increase ethanol productivity, we optimized the cellulase expression system.…”
Section: Research Articlementioning
confidence: 99%
“…The plasmid for cell surface display of the T. reesei EGII gene was constructed as follows. The DNA fragment encoding the secretion signal sequence from R. oryzae, the EGII gene, and the 3′ half of α-agglutinin was prepared by PCR using pEG23u31H6 [10] with the following primers: 5′-CATGCTAGCATGCAACTGTTCAATTTGCC ATTGAAAG-3′ and 5′-TCCCCCCGGGTTTGATT ATGTTCTTTCTATTTGAATGAGATATG-3′. The amplified fragment was digested with NheI and XmaI and ligated into pGK404 [15].…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these recombinant strains could directly utilize cellulose, as complete cellulose hydrolysis required synergistic action of at least three main cellulases (Cho et al, 2004;Mingardon et al, 2005;Arai et al, 2007). Fujita et al (2002Fujita et al ( , 2004 reported co-expression and surface display of cellulases in S. cerevisiae. The recombinant strain displaying three EG2 and CBH2 (derived from T. reesei), and the β-glucosidase (derived from Aspergillus aculeatus) enzymes could directly convert 10 g/l phosphoric acid swollen cellulose to approximately 3g/l ethanol.…”
Section: -Yeast Surface Display (Non-complexed Cellulase Systems Celmentioning
confidence: 99%
“…A recent paper comparing cellobiose usage by surface expressed versus secreted β-glucosidase demonstrated that expression on the yeast cell surface stabilized and increased specific activity of the enzyme [36]. Fujita et al, [37] reported co-display of endoglucanase II and β-glucosidase on the surface of S. cerevisiae MT8-1. The strain was able to grow on β-glucan as the sole carbon source and produced 16.5 g/l of ethanol without pretreatment, whereas the strains without the co-displayed enzymes did not grow.…”
Section: Surface-display For Biofuels Productionmentioning
confidence: 99%